2010
DOI: 10.1007/s12374-010-9122-y
|View full text |Cite
|
Sign up to set email alerts
|

Wild Relatives of the Wheat Grain Proteome

Abstract: We applied proteomics analysis to generate a map of the wild relatives of wheat grain proteins. These differentially expressed proteins are potentially involved in metabolism, stress responses, and other biological activities. Using two-dimensional electrophoresis, we detected 119, 134, and 193 reproducible spots on gels loaded with protein samples extracted from the A, B, and D genomes, respectively, of the mature grain. In all, 89, 53, and 54 distinct proteins, respectively, were found among these genomes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Recently, a comparative study between wild emmer and cultivated wheat under salt stress has evidently demonstrated that the transcription factors, such as NAC2F, NAC8, DREB3A, MYB3R, and MYB2A, showed higher level of gene expression and it is supported to a clear correlation between salt tolerance and wild emmer wheat that is put forward the importance of this wild genome . In a different aspect, Kim et al (2010) conducted a study to understand the genome x seed protein density interactions by using proteomic tool MALDI-TOF mass spectrometry. One of the convincible results was considerable amount of protein spots among A, B and D genome in wheat, and their functional ability annotated to important protein groups that were responsive under drought, cold and heat stress and pathogen attack related ones.…”
Section: Wheatmentioning
confidence: 99%
“…Recently, a comparative study between wild emmer and cultivated wheat under salt stress has evidently demonstrated that the transcription factors, such as NAC2F, NAC8, DREB3A, MYB3R, and MYB2A, showed higher level of gene expression and it is supported to a clear correlation between salt tolerance and wild emmer wheat that is put forward the importance of this wild genome . In a different aspect, Kim et al (2010) conducted a study to understand the genome x seed protein density interactions by using proteomic tool MALDI-TOF mass spectrometry. One of the convincible results was considerable amount of protein spots among A, B and D genome in wheat, and their functional ability annotated to important protein groups that were responsive under drought, cold and heat stress and pathogen attack related ones.…”
Section: Wheatmentioning
confidence: 99%
“…Around 68 of them could be considered as the novel findings, as they were not reported in earlier proteomics studies of normal wheat grains with or without any treatment, as well as the effect of abiotic and biotic stress conditions (Dupont et al, 2011;Gobaa et al, 2007;Grove et al, 2009;Guo e al. 2012;Kim et al, 2010;Skylas et al, 2005). Combined use of SDS-PAGE and LC-MS E techniques has been proposed to be more effective (Salekdeh and Komatsu, 2007) and previously utilized for profiling the complex flax seed proteome (Barvkar et al, 2012), insect gut proteome (Dawkar et al, 2011), and to understand the kiwi fruit ripening (Minas et al, 2012).…”
Section: Grain Proteins Analysis Through Combination Of Sds-page (1d)mentioning
confidence: 99%
“…Protein samples were mixed with an equal volume of SDS reducing buffer containing 0.625 mM Tris-HCl (pH 6.8), 2% SDS, 0.5% 2-mercaptoethanol, 30% glycerol, and 0.002% Bromophenol Blue for 1D-PAGE, separated by SDS-PAGE (Laemmli 1970;Yun et al 2008;Kim et al 2010b). The 4% stacking gel was overlaid on a separating gel (12% polyacrylamide at an acrylamide/bis acrylamide ratio of 30.0:0.8).…”
Section: Gel Electrophoresismentioning
confidence: 99%